2001
DOI: 10.1097/00003246-200106000-00015
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced fibrinolysis prevents the development of multiple organ failure in disseminated intravascular coagulation in spite of much activation of blood coagulation

Abstract: Enhanced fibrinolysis was considered to be the important defense mechanism in preventing the development of MOF in DIC. The increases in plasma levels of t-PA and PAI were poor prognostic markers in DIC. Further careful study may be useful to clarify whether the fibrinolytic therapy is beneficial in clinical DIC patients with MOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 18 publications
2
54
0
1
Order By: Relevance
“…The pathophysiology of DIC involves both the initiation of a fibrin thrombus and the inhibition of fibrinolysis, resulting in the persistence of intravascular thrombi (Levi et al, 1999). Both the coagulation and fibrinolysis phases are equally important in the development of DIC (Asakura et al, 2001). The main mechanism by which the body lyses fibrin thrombi involves plasmin, the activated form of plasminogen.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of DIC involves both the initiation of a fibrin thrombus and the inhibition of fibrinolysis, resulting in the persistence of intravascular thrombi (Levi et al, 1999). Both the coagulation and fibrinolysis phases are equally important in the development of DIC (Asakura et al, 2001). The main mechanism by which the body lyses fibrin thrombi involves plasmin, the activated form of plasminogen.…”
Section: Introductionmentioning
confidence: 99%
“…22 Inhibition of fibrinolysis by treatment with antifibrinolytic agents in this condition promotes microvascular thrombosis, resulting in organ failure. 23 In survivors of severe sepsis, markers of coagulation and fibrinolytic activation correlate, whereas in nonsurvivors coagulation activation is not balanced by activation of fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…23 In survivors of severe sepsis, markers of coagulation and fibrinolytic activation correlate, whereas in nonsurvivors coagulation activation is not balanced by activation of fibrinolysis. 22 In animal experiments, homozygous FVL provides no survival benefit in endotoxemia. 7 A possible explanation is that homozygous FVL exaggerates fibrin formation to a level that is above the threshold for effective clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Although activation of blood coagulation is a hallmark of DIC, the degree of this activation appears not to be related to the development of MOF. 78 In fact, suppressed fibrinolysis is believed to be one of the most important forebodes of MOF during DIC; low levels of a2 antiplasmin-plasmin complex and high values of PAI-1 could therefore function as markers of aggravating disease. 78,79 Various reports have especially recommended PAI-1 as a strong prognostic factor [80][81][82] and the level of the inhibitor may in part be genetically determined by the PAI-1 4G/5G polymorphism, which itself is associated with clinical outcome in meningococcal sepsis.…”
Section: Disseminated Intravascular Coagulationmentioning
confidence: 99%
“…78 In fact, suppressed fibrinolysis is believed to be one of the most important forebodes of MOF during DIC; low levels of a2 antiplasmin-plasmin complex and high values of PAI-1 could therefore function as markers of aggravating disease. 78,79 Various reports have especially recommended PAI-1 as a strong prognostic factor [80][81][82] and the level of the inhibitor may in part be genetically determined by the PAI-1 4G/5G polymorphism, which itself is associated with clinical outcome in meningococcal sepsis. 83 In spite of these candidate risk markers, a study by Leithauser et al 84 showed that at the onset of sepsis none of the haemostatic parameters TAT, antithrombin, protein C antigen and PAI-1 were associated with MOF.…”
Section: Disseminated Intravascular Coagulationmentioning
confidence: 99%